Anti-immigrantism in Western democracies : statecraft, desire and the politics of exclusion - Doty, Roxanne Lynn (Routledge/RIPE series in global political economy. Routledge/RIPE studies in global political economy, 2003)
This book critically examines the various practices of anti-immigrantism in three western democracies, the US, the UK and France, within the context of globalisation and questions our understanding of the state. Anti-Immigrantism in Western Democracies draws upon the works of Gilles Deleuze and Felix Guattari, and analyses their understanding of desire, its forms and its relation to the social order. Doty uses these concepts as a way to comprehend the forces at work in the social, political and economic life, to explore the impulses which move society towards various practices and policies, and finally to understand statecraft. In this innovative work the author concludes that immigration is an exemplary site of the manifestation of the desire for order and security in a world where things are perceived to be under threat and investigates the concept of neo-racism and its relationship to immigration policies. It will interest students and researchers of International Relations, Migration Studies and Cultural Studies.